Exploring real-world practices and challenges of sarcoma diagnosis in Morocco: A survey-based study among 144 pathologists - Kharmoum, Jinane; Idrissi Serhrouchni , Karima; Eliahai, Imane; Eljiar, Mohammed; Chraibi, Mariame (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Sarcoma diagnosis is a challenge for laboratories of cytopathology and anatomic pathology. We conducted this survey-based study to better elucidate real-world practices and challenges of sarcoma diagnosis. Methods: This was a cross-sectional study using an anonymous questionnaire. The survey was distributed among pathologists using snowball sampling. Descriptive statistics were used to report the finding of this survey. Results: A total of 144 Moroccan pathologists were surveyed. Most respondents were from academic institutions (41.7%) and those with a specialization in sarcoma diagnosis represented 57%, through training using post-graduate fellowships followed by internships abroad and inter-university diplomas. Remarkably, 36.8% of participants reported no training on sarcoma pathology during their career. Regarding frequency of sarcoma diagnosis, 64.6% of pathologists reported having received less than one case of sarcoma per week and more than 70% did not receive sufficient information from referring clinicians. The majority of pathologists reported their nonattendance in multidisciplinary meetings. Morphology and immunohistochemistry were the most frequently used diagnostic tools, while fluorescence in situ hybridization and other molecular biology techniques were accessible for only 27% and 20.1% of pathologists, respectively. Response time during pathological diagnosis of sarcoma was 14 days according to 52.8% of surveyed participants. In addition, a second opinion was needed for 66% of pathologists. Conclusions: Specialized training on sarcoma pathology in Morocco is lacking. A national working group on sarcoma pathology is needed to provide second opinions, and therefore, improve the management of this malignancy of poor prognosis. (www.actabiomedica.it)